Assessment of the role of micro-credit granted to women entrepreneurs towards poverty reduction the case study of pride Tanzania – Morogoro branch. - Thomas Nathan (Mzumbe University, 2024)
A Dissertation Submitted to Mzumbe University as a partial Fulfilment for the Requirements of award of the Degree of Master of Science in Accounting and Finance (MSc. A&F) of Mzumbe University.